Anthropometric-Based Ergonomic Assessment of Student Chairs to Prevent Musculoskeletal Discomfort - Taufik Ramadhan Fitrianto; Bahtiar Rahmat; Siska Anggiriani; Desy Mulyosari; Nurhanifah Nurhanifah; Alfani Risman Nugroho; Muhammad Afif Affandi (Jurnal SENOPATI : Sustainability, Ergonomics, Optimization, and Application of Industrial Engineering, 2026)
Many students at Politeknik Industri Furnitur dan Pengolahan Kayu have reported musculoskeletal discomfort after prolonged sitting in classroom chairs, including lower back pain, neck stiffness, and shoulder tension. These complaints suggest that the existing chairs may not accommodate users’ anthropometric characteristics. This study aimed to evaluate the ergonomic compatibility of current student chairs and to redesign their dimensions based on anthropometric data to meet both national and international ergonomic standards. The research was conducted through three main stages: (1) identifying discomfort areas using the Nordic Body Map (NBM) questionnaire, (2) collecting key body measurements from male and female students, and (3) performing a mismatch analysis between anthropometric dimensions and chair parameters. The analysis revealed a high level of mismatch—particularly in seat height, depth, and backrest dimensions—which correlated with the prevalence of MSD complaints. A redesigned chair model was then proposed based on student anthropometry and evaluated against available standards. The redesigned dimensions significantly reduced mismatch rates for both male and female users, indicating improved ergonomic compatibility. Alignment with international standards further supports the potential of this design to enhance comfort and reduce musculoskeletal risks. However, despite its functional improvements, the new chair proportions may appear less visually balanced, necessitating further refinement in aesthetic and structural aspects before implementation.